Faktor-faktor Kebijakan Myanmar Memilih Norwegia dalam Upaya Penyelesaian Konflik Etnik - Dewayanti, Itsnaini; Paramasatya, Satwika (Journal of International Relations, 2019)
Ethnic conflict is one of the main problems faced by Myanmar for years till nowadays. Solvingthe ethnic conflict, the Myanmar Government have arranged Nationwide Ceasefire Agreement (NCA). Yet, NCA is not effective because the violence still involves in some conflicts. To face and solve the ethnic conflict Myanmar Government decided another rational policy, which is asking the Norway Government to help solve and face the conflict and did not asking to other countries, such as China and India. Norway Government welcomed the request from Myanmar Government for cooperation activity Government of Norway made the policy called Myanmar Peace Support Initiative (MPSI). The purpose of this research is to analyse the reason of Myanmar Government asked Norway to help solve and face the conflict that still ongoing and did not choosing Myanmar’s neighbours, which are China and India. Besides that, this research will explain about the way Norway help to face and solve the ethnic conflict through MPSI. This research using rational choice theory and concept of national interest. Methodology on this research are literature study and internet basis. The result of this research is Myanmar chose Norway due to Norway’s assistance more supportive towards settlement of ethnic conflict in Myanmar than China and India.